Suppose,
\(\displaystyle f(x) = \sum_{n=0}^{\infty} f_n x^n\), \(\displaystyle F(n) = \sum_{r=0}^{n} f_{r}\) and \(\displaystyle \lim_{n \to \infty} \dfrac{F(n)}{n^{r_f}} = \text{d}_f \)
Similarly,
g(x)=n=0∑∞gnxn, G(n)=r=0∑ngr and n→∞limnrgG(n)=dg
From Monster Limit 2, we have,
{limx→1−(1−x)rf f(x)=df Γ(1+rf)limx→1−(1−x)rg g(x)=dg Γ(1+rg)
Now, consider the same quantities for fg(x)=f(x)g(x), i.e,
fg(x)=n=0∑∞fgnxn, FG(n)=r=0∑nfgr and n→∞limnrfgFG(n)=dfg
Again,
x→1−lim(1−x)rfg fg(x)=dfg Γ(1+rfg)
Prove That
dfg=dfdgΓ(1+rf+rg)Γ(1+rf)Γ(1+rg)
#Calculus
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.